1983
DOI: 10.1159/000265239
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytic Activity of Cultured Retinal Pigment Epithelial Cells from Chick Embryo: Inhibition by Melatonin and Cyclic AMP, and Its Reversal by Taurine and Cyclic GMP

Abstract: Cultured chick retinal pigment epithelial cells phagocytosed polystyrene latex particles. The phagocytosis was inhibited very specifically by melatonin, which attained 50% inhibition at about 10––16M. Other indole compounds such as 5-methoxytryptophol, 5-hydroxytryptophol, 6-hydroxymelatonin, N-acetylserotonin, 5-methoxytryptamine and serotonin were also inhibitory although their effects were less than 1/10,000 that of melatonin. Possible retinal neurotransmitters, acetylcholine, γ-aminobutyric acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(27 citation statements)
references
References 51 publications
0
26
1
Order By: Relevance
“…Melatonin has been found in the retina of several species (6)(7)(8)(9)(10). Retinal melatonin has been implicated in photoreceptor outer segment disc shedding and phagocytosis (11,12), melanosome aggregation in pigment epithelium (13), and cone photoreceptor retinomotor movement (14). Because so many important biological processes are regulated by melatonin, the mechanism by which this hormone acts is of great interest.…”
mentioning
confidence: 99%
“…Melatonin has been found in the retina of several species (6)(7)(8)(9)(10). Retinal melatonin has been implicated in photoreceptor outer segment disc shedding and phagocytosis (11,12), melanosome aggregation in pigment epithelium (13), and cone photoreceptor retinomotor movement (14). Because so many important biological processes are regulated by melatonin, the mechanism by which this hormone acts is of great interest.…”
mentioning
confidence: 99%
“…Melatonine and taurine were claimed to be the exgenous factors which control the enzyme activities mediating the cAMP and cGMP levels. Melatonine and taurine act via specific receptors on the plasmalemma, as was shown in vitro experiments using cultured RPE from chick embryo (23).…”
mentioning
confidence: 71%
“…The present investigation was initiated by a study of Ogino et al (23), which showed under in vitro conditions with cultured cells of the RPE an inhibition of phagocytosis by melatonine and a stimulation by taurine. It has been proposed that melatonine stimulates adenylate cyclase activity via a specific receptor on the plasmalemma resulting in an increase in the intracellular cAMP level as a second messenger that inhibits phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress caused by swimming to exhaustion provoked lower melatonin peak and consequently higher phagocytic activity of macrophages [61]. Melatonin also suppressed phagocytic activity of cultured retinal pigment cells [62].…”
Section: Amino Acid Hormonesmentioning
confidence: 99%